Acclimatization of Rhizophagus irregularis Enhances Zn Tolerance of the Fungus and the Mycorrhizal Plant Partner - Bui, Van Cuong; Franken, Philipp (Frontiers in Microbiology, 2018)
Arbuscular mycorrhizal (AM) fungi confer heavy metal tolerance to plants, but this characteristic differs between different AM fungal strains. We tested the hypotheses if acclimatisation of an AM fungus to Zn stress is possible and if this leads also to higher Zn tolerance of mycorrhizal plants. The AM fungus Rhizophagus irregularis was acclimatised in root organ cultures (Daucus carota L.) to Zn resulting in an acclimatised (Acc+) strain. The non-acclimatised (Acc-) strain remained untreated. Fungal development and RNA accumulation of a set of stress-related genes were analysed in root organ cultures and the capacity of conferring Zn tolerance to maize plants was investigated in pot cultures. Development of Acc+ strain was significantly higher than Acc- strain, when strains were grown in Zn-enriched root organ cultures, whereas the growth of the Acc+ strain was reduced on normal medium probably due to a higher Zn demand compared to the Acc- strain. RNA accumulation analyses revealed different expression patterns of genes encoding glutathione S-transferase (RiGST), superoxide dismutase (RiSOD) and glutaredoxin (RiGRX) between the two strains. Plants inoculated with the Acc+ strain showed higher biomass and lower Zn concentration than those inoculated with the Acc- strain. The results showed that R. irregularis can be acclimatised to increased amounts of Zn. This acclimatisation leads not only to improved fungal development in Zn-stress conditions, but also to an increase of mycorrhiza-induced Zn tolerance of colonised plants.